2003
DOI: 10.1021/es026236f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Randomly Methylated β-Cyclodextrin on Physical Properties of Soils

Abstract: The application of cyclodextrins in several soil remediation technologies has been increasingly studied, but little is known about their effects on soil physical properties. One of the popular soil remediation additives, randomly methylated beta-cyclodextrin (RAMEB), was found to significantly alter surface and pore properties of soil clay minerals. Therefore, in this paper we studied the effect of various RAMEB doses on physical properties of selected soils, representing a wide range of clay content (3-49%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Their findings suggested that the surface properties and pore structure of minerals changed dramatically when CyDs were introduced, leading to a decrease in surface area, an increase in adsorption energy, and decreases in the volumes of micro and mesopores. These authors also observed a great modification of physical properties in some selected soils after RAMEB addition, such as increasing water adsorption and surface area in sandy soils and their decreasing in clay soils, and an increasing proportion of coarse-size soil fractions owing to aggregation of smaller particles [49]. However, it has not been determined if certain surface and pore properties return to the original state after the removal of the CyD, either by leaching or by biodegradation, or if the phenomena observed for RAMEB are generally true for other CyDs.…”
mentioning
confidence: 87%
“…Their findings suggested that the surface properties and pore structure of minerals changed dramatically when CyDs were introduced, leading to a decrease in surface area, an increase in adsorption energy, and decreases in the volumes of micro and mesopores. These authors also observed a great modification of physical properties in some selected soils after RAMEB addition, such as increasing water adsorption and surface area in sandy soils and their decreasing in clay soils, and an increasing proportion of coarse-size soil fractions owing to aggregation of smaller particles [49]. However, it has not been determined if certain surface and pore properties return to the original state after the removal of the CyD, either by leaching or by biodegradation, or if the phenomena observed for RAMEB are generally true for other CyDs.…”
mentioning
confidence: 87%
“…Cyclodextrins are known for their affinity to complex with a wide range of chemical compounds, including heavy metals and organic pollutants (Cathum et al, 2005;Chatain et al, 2004;Jozefaciuk et al, 2003;Morillo et al, 2001;Tick et al, 2003;Villaverde et al, 2005aVillaverde et al, , 2005b. Like the free cyclodextrin, the cyclodextrin-based material contains molecular cavities and can include nonpolar molecules, such as PCBs, and polar chemicals, such as free ions of heavy metals.…”
Section: Exhibit 4 Particles Of Cyclodextrin-based Materials Under Thmentioning
confidence: 99%
“…There is growing interest in the use of cyclodextrins (CDs) for the cleanup of organic and inorganic pollutants in soils, sediment, and groundwater (Cathum et al, 2005;Chatain et al, 2004;Jozefaciuk et al, 2003;Morillo et al 2001;Tick et al, 2003;Villaverde et al, 2005aVillaverde et al, , 2005b. Cyclodextrins are polysaccharides produced from hydrolyzed starch that uses the external enzyme cyclodextrin glucanotransferase.…”
Section: Introductionmentioning
confidence: 99%
“…RAMEB also enhanced the biodegradation of mazout (distillation residue of oil refinery, formerly used as heating fuel) in occurring in a historically contaminated soil (Molnar et al 2003). RAMEB effect is attributed partly to its impact on the surface properties and porosity of the soils (Jozefaciuk et al 2003). RAMEB was found to be slowly biodegradable in soils, displaying about 1-year half-life time .…”
Section: Introductionmentioning
confidence: 99%